PEMANFAATAN TEPUNG KULIT PEPAYA (Carica papaya L) DALAM RANSUM TERHADAP KUALITAS INTERNAL TELUR - Paat, Armando; Sarajar, C.L.; Leke, J. R.; Sompie, F. N. (ZOOTEC, 2020)
UTILIZATION AND INTERNAL QUALITY OF EGG ON PAPAYA PEEL MEAL DIET (CARICA PAPAYA L). The aim of research was to utilization and internal quality of eggs on papaya (carica papaya L) peel meal diet. The material used in this study were one hundred laying hens (MB 402). The completely randomized design (CRD) was done in this research for analysing of statistics to five treatments and four replications, each replications was occupied by five laying hens (MB 402). The variable measured were egg weight, egg yolk, colour of egg yolk.Â  The result of this research showed that egg weight, egg yolk, the colour egg yolk was not significantly different (P>0.05). Conclusion, the utilization of flour skin papaya until 16% in feed will increase the quality of chicken eggs.Â Kata Kunci: Papaya peel meal, laying feed, the quality internal egg.